1978
DOI: 10.1016/s0022-5347(17)57179-7
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovesical Fistula after Ureterolithotomy: A Case Report and Review of the Literature

Abstract: A case is reported of massive recurrent hematuria after ureterolithotomy caused by a fistula between a branch of the hypogastric artery and the bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…In one case the fistula has gone to the one patient the nephrectomised kidney was autobladder. 70 A few have engaged the internal iliac artery transplanted. 51 and in one case a polar renal artery after Acusise In recent years there has been an increasing use of endopyelotomy.…”
Section: Ligature Of the Internal Iliac Artery Autotransplantationmentioning
confidence: 99%
“…In one case the fistula has gone to the one patient the nephrectomised kidney was autobladder. 70 A few have engaged the internal iliac artery transplanted. 51 and in one case a polar renal artery after Acusise In recent years there has been an increasing use of endopyelotomy.…”
Section: Ligature Of the Internal Iliac Artery Autotransplantationmentioning
confidence: 99%
“…2,3 Manipulation of the bladder, for example by cystoscopy or ureterolithotomy, may also cause fistulae. 4,5 In this unique case presented, a self-inserted foreign body was not only responsible for an arteriovesical fistula, but also for acute limb ischemia.…”
Section: Discussionmentioning
confidence: 92%
“…Arteriovesical fistulas can occur iatrogenic injury [2-6], secondary to trauma [1,7-9] and spontaneously [10,11]. Rous et al reported the first case of a ruptured posttraumatic pseudoaneurysm of the external iliac artery 1 week after a gunshot wound to the lateral aspect of the bladder [7].…”
Section: Discussionmentioning
confidence: 99%
“…Rous et al reported the first case of a ruptured posttraumatic pseudoaneurysm of the external iliac artery 1 week after a gunshot wound to the lateral aspect of the bladder [7]. Arteriovesical fistulas are mostly associated with previous pelvic surgeries [2-4], radiotherapy [5] and urologic interventions [6] in patients with vascular disease. There are only two cases where an arteriovesical fistula formed spontaneously due to a ruptured iliac artery aneurysm with hematuria as initial presentation [10,11].…”
Section: Discussionmentioning
confidence: 99%